2020
DOI: 10.1158/2159-8290.cd-20-0300
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Suppression of Transgenic T-cell Receptor Expression via Gamma-Retroviral Vector Methylation in Adoptive Cell Transfer Therapy

Abstract: Transgenic T-cell receptor (TCR) adoptive cell therapies recognizing tumor antigens are associated with robust initial response rates, but frequent disease relapse. This usually occurs in the setting of poor long-term persistence of cells expressing the transgenic TCR, generated using murine stem cell virus (MSCV) γ -retroviral vectors. Analysis of clinical transgenic adoptive cell therapy products in vivo revealed that despite strong persistence of the transgenic TCR DNA sequence over time, its expression was… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…However, loss of vector-driven transcriptional activity in cells containing proviral DNA has been observed early after transduction (52), which drastically limits the efficacy of vector-based gene delivery platforms. Although attempts to optimize vector design, particularly with γ-retroviruses, have augmented transgene expression, these systems remain susceptible to promoter shutdown (16,53).…”
Section: Bet Protein Blockade Improves the Production Of Cd19 Car T Cells From Poor-quality Lymphocytes In Patients With Cllmentioning
confidence: 99%
See 1 more Smart Citation
“…However, loss of vector-driven transcriptional activity in cells containing proviral DNA has been observed early after transduction (52), which drastically limits the efficacy of vector-based gene delivery platforms. Although attempts to optimize vector design, particularly with γ-retroviruses, have augmented transgene expression, these systems remain susceptible to promoter shutdown (16,53).…”
Section: Bet Protein Blockade Improves the Production Of Cd19 Car T Cells From Poor-quality Lymphocytes In Patients With Cllmentioning
confidence: 99%
“…The level and duration of cell-surface CAR expression may also be an important T cell-intrinsic factor influencing clinical efficacy, and receptor extinction as a potential mechanism of resistance has not been widely explored in the context of CAR T cell therapy. The half-life of transgenic antigen receptor expression has been previously implicated as a major determinant of clinical responses to TCR-engineered T cells (15,16). Transgene shutdown, as defined by an immediate silencing or a gradual decrease in gene expression after differentiation or proliferation of cells transduced with integrating viruses, can occur through multiple epigenetic processes, potentially leading to poor clinical responses to adoptive cell therapies (17).…”
Section: Introductionmentioning
confidence: 99%
“…Our results strengthen the notion that the molecular profiles of the cells used in adoptive cell therapy is of great value for determining treatment success. This approach has also been proposed for immune checkpoint inhibitors ( 13 , 14 ). Thus, biomarkers of the efficacy of adoptive cell therapy, similar to those cited here ( 5–9 , 37 ), and the DNA methylation markers discovered in our study almost certainly await discovery.…”
Section: Discussionmentioning
confidence: 99%
“…DNA methylation is altered in cancer ( 10 , 11 ), affecting the immune system and immunotherapy efficacy ( 12 ). In this regard, DNA methylation signatures are associated with clinical response to programmed cell death protein 1 checkpoint blockade ( 13 ) and the DNA methylation status of the vector for transgenic T-cell receptor adoptive cell therapy relates to changes in tumor burden ( 14 ). For these reasons, we decided to assess the effects of the DNA methylation landscape of preinfused CART19 cells on the clinical outcome of patients with B-cell malignancies.…”
mentioning
confidence: 99%
“…Similarly, in a child with junctional epidermolysis bullosa, the human epidermis can be regenerated entirely by autologous transgenic keratinocyte cultures via retroviral vectors 297 . Another clinical study indicated that γ retroviral vector showed epigenetic suppression of transgenic T-cell receptor expression through the vector methylation in adoptive cell transfer therapy 298 . Moreover, the anticancer vaccine based on an alphaviral vector enhanced HER2-specific memory CD8 + T cells and exhibited obvious inhibition of breast cancer in clinical testing 299 .…”
Section: Clinical Trialsmentioning
confidence: 99%